Shifting into digital services: Does a crisis matter and for who? - Erik van der Marel (European Centre for International Political Economy (ECIPE), 2020)
How do trade patterns change after an external shock such as an economic crisis, and is this shift structural? This paper uses a Difference-in-Difference (DID) approach to investigate whether services trade became more digital after the Global Financial Crisis (GFC) in 2008. It finds that the GFC formed an independent break from the previous period that turned services trade to become more digital - although there are signs that this somewhat already happened before 2008. Software-intense services such as R&D services, information services, computer services and charges for Intellectual Property Rights (IPR) saw on average a 6 percent higher increase in global exports compared to other non-digital sectors post-2008. Countries with higher internet usage and with already comparative advantage in these sectors saw this higher increase in digital trade. More striking is that in particular upper-middle income countries and countries with high manufacturing activity saw the sharpest shift into digital services trade after the GFC. These significant outcomes forecast a direction into which patterns of services trade are likely to turn after the current economic crisis resulting from COVID-19.
Keywords: 330; Economic crisis; shock; coronavirus; financial crisis; digitalization; Wirtschaftskrise; Schock; Coronavirus; Finanzkrise; Digitalisierung